Student and Teacher Evaluation of a School Re-entry Program Following the Initial Covid19 Lockdown. (December 2021) - Capurso, Michele; Buratta, Livia; Pazzagli, Chiara; Pagano Salmi, Luciana; Casucci, Simone; Finauro, Stefania; Potenza, Cristina; Mazzeschi, Claudia
The Covid19 pandemic raised concerns regarding millions of children's mental health. For schools, the real challenge has been how to manage the situation in terms of education and development. The present investigation was carried out to evaluate a school re-entry program that supported teachers and students with activities aimed at processing emotions and lockdown experiences in their classrooms. Results show that the program was well perceived and was associated with a consequent reduction in children's state anxiety and negative emotions. We conclude that a school re-entry program can play an important role in fostering resilience and development during a crisis.